The Impact of Digital Advertising on Consumer Behavior: An Applied Study on Social Media Users - Al-Dawsari, Sara Saad; Al-Shuwaikhat, Sadiq Ali Mubarak (Journal of Humanities & Social Sciences, 2025)
The research aimed to demonstrate the impact of online service marketing on consumer behavior, help those interested in this field to understand this topic, and demonstrate the steps of online service marketing. The research used the descriptive analytical approach. The research relied on questionnaires in its tools. The questionnaire was distributed to a sample of 55 social media users. The study reached a number of results, including that all (T-test) values were higher than the table value (2000), except for a phrase related to gifts and appreciation shields. The second hypothesis was confirmed, which indicates that moral incentives positively affect job satisfaction. The third hypothesis related to job satisfaction was rejected, although all (T-test) values were higher than the table value (2000). Based on the results, the researcher presented a number of recommendations, including: Developing appropriate content. Companies should develop marketing content that is relevant and useful to consumers, with a focus on providing real value that meets the needs and expectations of customers. Using targeted advertising. It is important for companies to use targeted advertising to increase the effectiveness of their marketing campaigns, allowing for the best results at the lowest costs. Enhancing customer interactions: Companies must enhance customer interactions and communication to build long-term relationships and increase customer loyalty to the brand.